2010
DOI: 10.1111/j.1872-034x.2010.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of double filtration plasmapheresis in combination with interferon therapy for chronic hepatitis C

Abstract: The cEVR results in this study suggest that high rates of sustained virological response can be achieved in retreated and treatment-naïve patients using DFPP in combination with PEG-IFN/RBV therapy. Results indicate that this therapy could be safely conducted, even in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…In DFPP + PEG-IFN therapy, viral reduction after 4 weeks of treatment has been 2.43 ± 1.07 log IU/ml with overall SVR achieved in 70.8% (17/24) of patients [3], and 2.79 ± 1.85 log IU/ml with cEVR in 57.5% (104/181) [4]. The current study showed a viral reduction of 3.24 ± 1.00 log IU/ml with a cEVR rate of 45% (8/20 patients).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In DFPP + PEG-IFN therapy, viral reduction after 4 weeks of treatment has been 2.43 ± 1.07 log IU/ml with overall SVR achieved in 70.8% (17/24) of patients [3], and 2.79 ± 1.85 log IU/ml with cEVR in 57.5% (104/181) [4]. The current study showed a viral reduction of 3.24 ± 1.00 log IU/ml with a cEVR rate of 45% (8/20 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Re-treatment with PEG-IFN-α2a/RBV of 107 relapsers to PEG-IFN/RBV therapy has achieved cEVR in 43% [22]; re-treatment with PEG-IFN-α2a/RBV of 469 relapse and NVR patients to PEG-IFN-α2b/RBV has achieved cEVR in only 13% [23]. Re-treatment with DFPP + PEG-IFN/RBV of 73 relapse and NVR patients to previous PEG-IFN/RBV therapy has achieved cEVR in 63.0% of relapsers and in 18.9% of NVR patients [4]. Therefore, it is expected that the addition of DFPP to PEG-IFN/RBV therapy will be effective in the re-treatment of relapse and NVR patients to previous PEG-IFN/RBV therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of DFPP and IFN also achieved impressive SVR in difficult-to-treat patients (i.e., relapsed, nonresponder, or HIVcoinfected patients) [181][182][183][184] and may also be safe for the elderly population [185]. However, the approach of apheresis for decreasing HCV viral load requires specialty equipment and possesses potential risk of adverse events (e.g., blood pressure lowering, puncture site hematoma, or infection) [181,185].…”
Section: Therapeutic Apheresis For the Removal Of Hcv Virionsmentioning
confidence: 99%
“…The use of double-filtration plasmapheresis (DFPP), approved in Japan in April 2008 for the retreatment of chronic CHC patients with genotype 1b and high viral loads, together with IFN administration has produced a substantial reduction in the viral load during the early stages of treatment and has effected a high sustained virological response (SVR) [8,9], suggesting that this treatment is a new modality for difficult-to-treat CHC patients.…”
Section: Double-filtration Plasmapheresismentioning
confidence: 99%